Conditions for building a community of practice in an advanced physics laboratory - Irving, Paul W.; Sayre, Eleanor C. (My University, 2014)
We use the theory of communities of practice and the concept of accountable disciplinary knowledge to describe how a learning community develops in the context of an upper-division physics laboratory course. The change in accountable disciplinary knowledge motivates students’ enculturation into a community of practice. The enculturation process is facilitated by four specific structural features of the course and supported by a primary instructional choice. The four structural features are “paucity of instructor time,” “all in a room together,” “long and difficult experiments,” and “same experiments at different times.” The instructional choice is the encouragement of the sharing and development of knowledge and understanding by the instructor. The combination of the instructional choice and structural features promotes the development of the learning community in which students engage in authentic practices of a physicist. This results in a classroom community that can provide students with the opportunity to have an accelerated trajectory towards being a more central participant of the community of a practice of physicists. We support our claims with video-based observations of laboratory classroom interactions and individual, semistructured interviews with students about their laboratory experiences and physics identity.
Keywords: Community of practice; Learning community; Physics laboratory course; Accountable disciplinary knowledge